GROWTH ANALYSIS OF BEAN CULTIVAR BR IPAGRO 44 GUAPO BRILHANTE IN FOUR SOWING DENSITIES GROWN IN THE SUMMER SEASON IN SANTA MARIA-RS - Zabot, Lucio; Dutra, Luiz Marcelo Costa; Jauer, Adilson; Lucca Filho, Orlando Antônio; Uhry, Daniel; Stefanelo, Cassiano; Losekan, Marno Elisandro; Farias, Juliano Ricardo; Ludwig, Marcos Paulo (Revista de Ciências Agroveterinárias, 2004)
Common bean cultivar BR-IPAGRO 44 Guapo Brilhante, type II, was grown during the summer season of 2001 in Santa Maria-RS, in four plant populations (200, 300, 400, and 500 thousand plants ha-1) with the objective of observing the behavior of some physiological traits, through the growth analysis technique. The experimental design was a randomized complete block, with four replications. Dry matter accumulation tended to be the same sometime among the populations. Leaf Area Index (LAI) and Net Assimilation Rate (NAR) were inversely related, but not at the same magnitude. The increase of plant density causes a thinner and denser leaf layer at the upper part of the canopy.